Six smartness dimensions in cultural management: social/cultural environment perspective - Pauliukevičiūtė, Audronė; Jucevičius, Robertas (Business, Management and Economics Engineering, 2018)
Cultural management as a complex process is constantly facing social/cultural challenges (policy shifts, creativity, interest coherence, the rise of technological capital, cultural emigration, etc.) that affect the growing need and importance for smartness in management. There is a lack of inter-disciplinary research on smartness in the context of cultural management. The goal of this article is to ground smartness dimensions in cultural management in the context of changing the social/cultural environment. Strategy, Creative Development, Harmonization of Interests in the Cultural Sector, Empowered Cultural Sector Parties, Harmony of Intellectual and Technological Capital as well as the Culture of Shared Value Creation are presented in this article as six smartness dimensions in cultural management (the management of cultural sector and the cultural policy implementation at the state level). The object of the work – smartness dimensions in cultural management. Principal objectives: critically analyse a variety of concepts of cultural management; reveal the importance of smartness in cultural management in the context of changing social/cultural environment; explore the characteristics of smartness dimensions in cultural management. Methods employed: critical literature analysis and meta-analysis. Research conducted by authors of this article allowed to ground smartness dimensions as factors, possibly determining a more successful cultural management.